Identification of prognostic factors for Krukenberg tumor - Weiqi Lu; Lei Yuan; Xishi Liu; Sun-Wei Guo (Wolters Kluwer Medknow Publications, 2013)
Aims: A Krukenberg tumor (KT) is an uncommon type of ovarian cancer (OC) with poor prognosis. We sought to identify prognostic factors for KT originating from primary gastrointestinal (GI) tumors. Methods: Forty-four patients with KT were assessed with follow-up. The primary endpoint was overall survival (OS) after first gynecological or GI surgery. Results: The use of postoperative chemotherapy, unilaterally involved ovarian mass, resection of primary tumors, absence of metastatic residuals, and diagnosis of GI tumors synchronously with or after gynecological surgery were identified to be prognostically favorable. For OS after the first cancer-related surgery, only the resection of primary tumor and absence of metastatic residuals were found to be favorable prognostic factors. The use of postoperative chemotherapy correlated with intraoperative intraperitoneal use of chemotherapy, but not with patients' clinicopathological characteristics, which were not found to be associated with any factors. Conclusion: The prognostic value of a factor depends on how survival is defined. Optimal cytoreductive surgery followed by aggressive chemotherapy may improve survival in KT patients. KT patients with unilaterally involved ovarian mass, resected primary tumors, and the absence of metastatic lesion residuals also seem to have a more favorable prognosis.